Structural Performance of Reinforced Concrete Voided One-Way Slab Under Static Loads - Awad, Fatima Hussien; Jabir, Hussain A. (Salehan Institute of Higher Education, 2026)
This study investigates the response of Reinforced Concrete (RC) voided one-way slabs under four-point bending, focusing on a novel and simple strengthening technique using embedded steel plates. Seven slab specimens were constructed with identical dimensions: 2000 × 600 × 130 mm. One specimen was a solid slab, serving as the control, while the remaining six were voided slabs. Among the voided slabs, one lacked a steel plate, and the other five were strengthened with steel plates of 1-, 2-, and 3-mm thickness. The primary objective of this study was to investigate whether the steel plate could compensate for the loss of strength and mitigate the impact of reducing the slab cross-section. The unstrengthened voided slab demonstrated substantial performance degradation compared to the reference solid slab, with 57% greater deflection at service load and significant reductions in ultimate load, stiffness, ductility, and toughness of about 23.5%, 25.4%, 10%, and 35%, respectively. Conversely, slabs strengthened with steel plates demonstrated a notable performance improvement. This was achieved by increasing flexural stiffness and reducing deflection at service load, with reductions ranging from 16% to 32% across the strengthened specimens. The percentage increase in ultimate strength ranged from 24% to 46% compared to the unstrengthened sample. Finally, a Finite Element Analysis (FEA) was performed using ABAQUS to validate the experimental results.